Dynamics of CD4-1+ and CD4-2+ lymphocytes in vaccinated ginbuna crucian carp Carassius auratus langsdorfii followed by cyprinid herpesvirus-2 (CyHV-2) challenge - Lik Ming, Lau; Hiroaki, Saito; Motohiko, Sano; Goshi, Kato (Elsevier Ltd., 2023)
Fish have two distinct CD4s: CD4-1 resembles the mammalian CD4 whereas CD4-2 is a second CD4 homolog. However, their roles in fish remain unclear. Ginbuna is susceptible to CyHV-2, whereas this infection can be prevented by a live-attenuated vaccine (P7-P8 strain). In this study, we investigated the dynamics of CD4-1+ and CD4-2+ lymphocytes in ginbuna vaccinated with P7-P8 and subsequently challenged with a virulent CyHV-2. The trunk-kidney and spleen of ginbuna were sampled at 1, 4, 7, 14, and 21 days post-vaccination (dpv) with P7-P8. The virulent CyHV-2 challenge was performed at 21 dpv and the same tissues were sampled at 1, 3, and 5 days post-infection (dpi). At every time point, leukocytes of the sampled tissues were stained with monoclonal antibodies against CD4-1 (6D1) and CD4-2 (D5) and analyzed by flow cytometry. The mortality of ginbuna were recorded daily after vaccination and virus challenge. The virulent CyHV-2 challenge test showed 90% and 10% survival in the vaccinated and control groups, respectively. After the P7-P8 vaccination, the fold-change increases in CD4-1+ lymphocytes (2 to 4-fold) in the trunk-kidney and spleen were much higher than those of CD4-2+ lymphocytes (1 to 2-fold). After the virulent CyHV-2 challenge, the fold-change increases in CD4-2+ lymphocytes were immediately observed at 1 dpi in the trunk-kidney (1.2-fold) and spleen (2-fold). However, a 0.2-fold increase and a 0.4-fold decrease in CD4-1+ lymphocytes were observed in the trunk-kidney and spleen, respectively. These results suggest that CD4-2+ lymphocytes can have a different role from CD4-1+ lymphocytes in fish.